India’s COVID-19 vaccination programme: challenges and solutions - Suryawanshi, Deodatt M.; Venugopal, Raghuram; Anbazhagan, Suguna; Rajseharan, Divya; Kumar, Gayathri (International Journal Of Community Medicine And Public Health, 2021)
Following January 2020, the SARS-COV-2 spread worldwide, ravaging health systems and causing widespread disruptions in the economic and social spheres. Successive waves of the COVID-19 pandemic in different countries concluded that the fight against the virus will be prolonged. Countries including India tried to reduce the spread of SARS-COV-2 by inducing restrictions on population mobility, high testing rates and dynamic algorithmic management but vaccination remained the only definitive answer against SARS COV-2. Though India started its vaccination program in a phased manner as early as January 2021, the second covid wave thwarted its gains with Indian facing a triple whammy of high incident cases, overburdened health infrastructure and inelastic vaccine supplies. In this review, we examined the strength, weakness, opportunities and threats (SWOT) of India’s vaccination programme and also suggest solutions to augment its strengths, manage its weakness, consolidate on opportunities and neutralise threats with effective measures of priority vaccination in high-risk districts, war footing immunisation, emergency use authorisation of vaccines, expanding vaccination programme to include children above 12 years and countering vaccine hesitancy with fact and reason. The review concluded that by strategic immunisation of high priority/high-risk districts the upcoming third wave can be thwarted if not completely prevented at a lower economic and social cost.